Tensor method of traffic management problems solving with service quality network parameters maintenance - Стрелковская, Ирина Викоторовна; Соловская, Ирина Николаевна (Eastern-European Journal of Enterprise Technologies, 2011)
Solution of traffic management problems with the help of tensor methods in NGN networks has been proposed. Traffic management problem in the network with the help of tensor model, represented in coordinate system of branches, basis contours and nodal pairs has been considered